Intelligent channel aware malicious free data forwarding scheme over wireless sensor networks - Sirajuddin, Mohammad (International Journal of Engineering and Technology, 2017)
In the communicative world each and every individual needs to perform global communication with failure-free intelligent model. Wireless Sensor Network, a medium which provides efficient communication modes to clients to satisfy their communication needs. However, this kind of wireless network channels are also facing lots of communication issues by means of several fault strategies, such as: link failures, node failures, bandwidth inefficiency, poor energy level, attacks and many more. So that, a fast growing network scheme is required as well as it provides lots of features to communication strategies and routing protocols, called Intelligent-Channel-Aware-Reputation Scheme [ICARS]. In the proposed system, the main objective is to provide the strong and failure-free wireless communication medium over networking with multiple numbers of nodes. As well as to provide high-level of security while the data is communicating from source to destination. For that powerful cryptographic algorithm is employed, called Modified Rijndael Algorithm (MRA) and to clearly state that the attack-free wireless communication channel with the help of intelligent routing strategies such as Route Request (RREQ) and Route Response (RREP).